2003, Las Vegas, NV July 27-30, 2003 2003
DOI: 10.13031/2013.13701
|View full text |Cite
|
Sign up to set email alerts
|

Citrus Yield Mapping System Using Machine Vision

Abstract: The authors are solely responsible for the content of this technical presentation. The technical presentation does not necessarily reflect the official position of the American Society of Agricultural Engineers (ASAE), and its printing and distribution does not constitute an endorsement of views which may be expressed. Technical presentations are not subject to the formal peer review process by ASAE editorial committees; therefore, they are not to be presented as refereed publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
4
1
Order By: Relevance
“…The results from the algorithm using the logistic regression classifier showed that the R 2 value between the count of dropped fruit and the actual number of fruit was 0.87. Other reported R 2 values were 0.76 by Annamalai and Lee (2003), 0.79 by Annamalai et al (2004), and 0.83 to 0.88 by Stajnko et al (2004). For correctly identified citrus fruit, this study showed a much higher rate (88.1%) than Patel et al (2012), who reported 69% (i.e., a 31% error rate).…”
Section: Accuracy Of Counting and Mass Estimationcontrasting
confidence: 48%
See 2 more Smart Citations
“…The results from the algorithm using the logistic regression classifier showed that the R 2 value between the count of dropped fruit and the actual number of fruit was 0.87. Other reported R 2 values were 0.76 by Annamalai and Lee (2003), 0.79 by Annamalai et al (2004), and 0.83 to 0.88 by Stajnko et al (2004). For correctly identified citrus fruit, this study showed a much higher rate (88.1%) than Patel et al (2012), who reported 69% (i.e., a 31% error rate).…”
Section: Accuracy Of Counting and Mass Estimationcontrasting
confidence: 48%
“…Fruit recognition using outdoor images in open areas, however, is challenging because object colors in images vary greatly under different illumination conditions. Many studies of fruit detection in outdoor images have shown reduced performance (Annamalai and Lee, 2003;Annamalai et al, 2004;Stajnko et al, 2004;Patel et al, 2012). Annamalai and Lee (2003) developed a citrus yield mapping system using machine vision with outdoor imaging.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a common modification is the addition of guidance systems to tractors and combines, which add the ability to accurately map fields and allow for the creation of planting and fertilizer prescriptions [3]. Additionally, these systems can be used to track yields for making field management decisions [4]. Other examples of modifications include adding modern fertilizer application equipment and technologies to planters [5], installing grain-saver kits to combines [6], implementing row-following technology to headers [7], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Similar studies were done by Safren et al (2007), who used multi-spectral images of the apple trees. Annamalai and Lee (2003) created an algorithm for image analysis to estimate citrus distribution in an orchard. The main aim of the work was to count the citrus fruit captured by a digital image.…”
Section: Introductionmentioning
confidence: 99%